Students’ Social Media Preferences as Secondary Learning Sources for Learning English (a Survey on Aceh English Major Undergraduate Students) - Katiara Katiara; Mulyadi Syahputra; Said Miftahul Fahmi (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to examine the preferences of undergraduate English students in Aceh in utilizing social media as a secondary learning resource in English learning. The study used a descriptive quantitative approach with data collection techniques through questionnaires distributed to English students from several universities in Aceh. Data were analyzed descriptively to identify the types of platforms used, the purposes of use, and students' perceptions of the benefits of social media in language learning. The results show that social media plays a significant role as a supplementary learning resource outside of formal classroom learning. The most frequently used platforms include WhatsApp, Instagram, TikTok, YouTube, Facebook, Telegram, and X, which are used for vocabulary development, listening and speaking practice, reading improvement, and writing skills. Students tend to choose platforms that are easily accessible, interactive, flexible, and provide authentic English content. These findings confirm that the use of social media encourages the development of digital literacy and student learning autonomy. This study provides an empirical contribution to the development of technology-based English learning strategies and serves as a reference for educators and educational institutions in integrating social media more effectively in the learning process.